Strengthening National Resilience Through Civic Education in the Era of Globalization - Jeremy Dimas Pamuja Harjanto; Damar Aji Saputra; Suparmi (Annujum: Journal of Humaniora and Law, 2025)
With globalization and technological advances, the character and identity of Indonesia's younger generation are being strongly influenced. This can threaten national resilience. Civic education is crucial for developing moral citizens who are aware of their rights and obligations, and love their country. This research employed a literature review, using journals as references. Data collection involved searching Google Scholar and publishing or perishing with the keywords civic education and national resilience in the era of globalization from 2021 to 2025. The study shows that civic education helps strengthen national resilience by enhancing national values, character, and understanding of national defense in the era of globalization.